Pengaruh Penambahan Oli Bekas Pada Aspal CPHMA Dengan Variasi Perendaman - Zangaji, Indra; Yunus, Ahmad Yauri; Nurdin, Abd Rahim (Program Studi Teknik Sipil Universitas Bosowa, 2025)
Cold Paving Hot Mix Asbuton is a mixture of asbuton consisting of aggregate, grainy asbuton, rejuvenator, and other additional materials mixed hot and laid cold. Asbuton Cold Paving Hot Mix (CPHMA) is a ready to use asphalt mixture product used as a surface layer for low traffic volume road pavement. This study aimed to calculate and analyze the effect of adding waste used oil to the hot asphalt mixture type CPHMA with soaking time variation on the value of asphalt mixture/marshall properties. This research used used oil with oil content of 5%, 10%, and 15%. Testing was carried out using the Marshall test apparatus. The results showed that the soaking time variation affects the mechanical properties of CPHMA asphalt. The longer the soaking time, the lower the properties of the mixture. The effect of used oil as an additive in the CPHMA asphalt mixture with the best soaking time and the maximum result is obtained when soaked for 5 days with 5% used oil content.